Use of Restorative Materials in Primary Teeth - A Retrospective University-Based Study - Luciana Antonio Pion; Raquel Assed Bezerra Segato; Paulo Nelson-Filho; Léa Assed Bezerra da Silva; Alexandra Mussolino de Queiroz; Francisco Wanderley Garcia Paula-Silva (Association of Support to Oral Health Research (APESB), 2023)
Objective: To investigate the types of restorative materials used for restorative treatment in primary teeth through a retrospective university-based study. Material and Methods: The sample consisted of all clinical records of children attended at the Pediatric Dentistry Clinic at the School of Dentistry of Ribeirão Preto at the University of São Paulo in Brazil. Inclusion criteria were primary anterior and posterior teeth that received dental restorations for treatment of dental caries lesions, dental trauma or dental development defects from 2013 to 2018. Restoration repairs and interim restorations during this period were also recorded. Descriptive analyzes were performed to assess the distribution according to the type of restorative material used over the years. Results: A total of 5,236 restorative procedures were performed in primary teeth, including restoration repair and interim restorations. Of those, 69% were done in posterior teeth and 31% in anterior teeth. Sixty percent of the procedures performed during this period were made of composite resin and a lower percentage of glass ionomer cement (18%) followed by silver amalgam (1%). The number of interim restorations was smaller but proportional to those of composite resin over the years. Conclusion: A tendency to carry out restorative treatment of primary teeth with composite resin during the 6 years of follow-up was observed.